RSR Calculator, a tool for the Calibration / Validation activities - C. Durán-Alarcón; A. Santamaría-Artigas; N. Valenzuela; C. Mattar (Revista de Teledetección, 2014)
The calibration/validation of remote sensing products is a key step that needs to be done before its use in different kinds of environmental applications and to ensure the success of remote sensing missions. In order to compare the measurements from remote sensors on spacecrafts and airborne platforms with in-situ data, it is necessary to perform a spectral comparison process that takes into account the relative spectral response of the sensors. This technical note presents the RSR Calculator, a new tool to estimate, through numerical convolution, the values corresponding to each spectral range of a given sensor. RSR Calculator is useful for several applications ranging from the convolution of spectral signatures of laboratory or field measurements to the parameter estimation for the calibration of sensors, such as extraterrestrial solar irradiance (ESUN) or atmospheric transmissivity (τ) per spectral band. RSR Calculator is a useful tool that allows the processing of spectral data and that it can be successfully applied in the calibration/validation remote sensing process of the optical domain.